Modeling a Century of Change: Kangerlussuaq Glacier's Mass Loss From 1933 to 2021 - E. Y. H. Lippert; M. Morlighem; G. Cheng; S. A. Khan (Geophysical Research Letters, 2024)
Abstract Kangerlussuaq Glacier (KG) is a major contributor to central‐eastern Greenland mass loss, but existing estimates of its mass balance over the last century are inconsistent, and specific drivers of change remain poorly understood. We present a novel approach that combines numerical modeling and a 1933–2021 climate forcing to reconstruct its mass balance over the past century. The model's final state aligns remarkably well with present‐day observations. The model reveals a total ice mass loss of 285 Gt over the past century, equivalent to 0.68 mm global sea level rise, 51% of which occurred since 2003 alone. Dynamic thinning from ice front retreat is responsible for 88% of mass change since 1933, with short‐term ice front variations having minimal impact on centennial mass loss. Compared to earlier studies, our findings suggest that KG lost 59% (or 301 Gt) less mass over the century than previously thought.